O uso de inovações em serviços bancários digitais - Massmann, Giovana Marise Colombelli (2018)
This study analyzes the use of digital banking innovations offered by a specific financial institution that do not adapt to market change, especially about technological innovations in customer service, will have their operational efficiency reduced and will lose market to those that present faster, useful, practical and profitable solutions. Through quantitave research methods, the aim of this study was to determine and analyze the use of digital tools, with on-line service via chat and video conferencing, offered by a financial institution for client's use through internet and mobile. Among the high-income client, it was possible to identify the profile of those who joined the use of new technologies. In the study, it was also described the research methodology, showing that it was made a quantitative analysis, by the collection of statistical data. The data analysis confirmed that there was a change in the percentage of use of the digital innovations offered, and that there of the client's relantionship with the financial institution, and the use of the new technologies. In addition, it was identified that it is feasible to carry out further research on the subject to confirm that different innovations may present different prespectives of use.